2017
DOI: 10.2528/pierc17032705
|View full text |Cite
|
Sign up to set email alerts
|

Circular Slotted Elliptical Patch Antenna With Elliptical Notch in Ground

Abstract: Abstract-A circular slotted elliptical patch antenna with an elliptical notch in ground for L-band and S-band application is presented. The proposed antenna consists of an elliptical patch with a circular notch on the top layer of a substrate, and a wide elliptical slot and an elliptical notch with two symmetrical slots on the bottom layer of the same substrate. The proposed antenna was fabricated on an FR-4 substrate (tan(δ)= 0.02,ε r = 4.3) with the thickness of 1.6 mm, and it was excited by coaxial feed joi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…The current at lower frequency is generated because of the edges of the patch. Lower, upper and resonant frequencies f is calculated by following equations [27] …”
Section: Prototyping and Results Discussionmentioning
confidence: 99%
“…The current at lower frequency is generated because of the edges of the patch. Lower, upper and resonant frequencies f is calculated by following equations [27] …”
Section: Prototyping and Results Discussionmentioning
confidence: 99%
“…The current at lower frequency is generated because of the edges of the patch. Lower, upper and resonant frequencies f are calculated by following equations [22]…”
Section: Current Distributionmentioning
confidence: 99%
“…S. Ur Rahman et al designed a wideband antenna with single band notch characteristics. Vikas et al explained the elliptical disc antenna with defected ground plane for UWB applications and antenna covers the frequency range from 2.94 to 12.57 GHz, similarly B. K. Shukla et al also demonstrated the circular slotted elliptical shaped antenna with elliptical notched ground plane for L and S‐band applications. H. M. Mansour et al illustrated the lotus shaped antenna for ultra wideband communication system from 1.42 to 10.0 GHz.…”
Section: Introductionmentioning
confidence: 99%
“…By thoroughly reviewing the aforementioned literature, the authors are inspired from the shape of antenna designed in Reference . It has been observed that antenna designed in Reference has explained the elliptical shaped antenna for UWB applications from the frequency range 2.94 to 12.57 GHz but has not illustrated the filtering concept which is required to remove the interference from the UWB frequency range.…”
Section: Introductionmentioning
confidence: 99%